POST-TRUTH ONTOLOGI POST-TRUTH DIALEKTIKA ANTARA ESENSI KEBENARAN DAN ENTITAS KEBENARAN DALAM FENOMENA PEMILIHAN PEMIMPIN - Hidayat, Ainur Rahman (Research Institute and Community Engagement of UIN MADURA, 2024)
The entity of truth in post-truth Indonesia is often analysis and interpreted separately from its way of being, both on a national and international scale. Such an understanding of the truth of the post-truth phenomenon always leads to the entity of solipsistic truth, because the post-truth phenomenon ontologically does not arise in a vacuum in the process of its interpretation, but rather exists alongside non-post-truth phenomena. In addition, the truth entity of the post-truth phenomenon is inherently also a very vague knowledge about reality, facts, and data. The truth entity of the post-truth phenomenon can be understood through the approach of three basic characteristics of truth analysis ontologically, namely facticity, understanding, and fallenness. The meaning of the truth of the post-truth phenomenon in Indonesia becomes increasingly unclear when the existence of the truth entity and the essence of truth are merely assumed without knowing the distinction between them. Understanding certain truth entities is part of ontological analysis, which concerns the meaning of truth and the way of existing in a particular world, for example, the truth entity of the political world. Meanwhile, understanding the essence of truth is part of ontic analysis, which concerns what truth actually is. Ontic analysis of the essence of truth is an analysis that results from all meanings of truth in all specific truth entities.